Pharmacy Performance Based on Financial Perspective Before and During COVID-19 Pandemic : A Case Study - Sartika Dasopang, Eva; Fauziah, Ida; Hasanah, Fenny; Natalia Siahaan, Desy; Rasyida Lubis, Dina Yunisma (Pharmaceutical Sciences and Research, 2022)
A pharmacy, aside from being a pharmaceutical care provider is also a functioning business. Thus, in the scope of business, pharmacy performance can be analysed using liquidity, activity, and profitability ratios. This study aimed to determine the performance of Pharmacy X based on a financial perspective before and during the COVID-19 pandemic. This research is a descriptive cross-sectional study that employed data obtained from sales and purchase records. The data were analysed using financial ratio analysis methods, including liquidity, activity, and profitability ratios. This study was conducted at Pharmacy X based on the amount of prescription and non-prescription income from before the COVID-19 pandemic (in 2019) and during the pandemic (in 2020). The results showed that Pharmacy X was not good at managing its current assets and current liabilities during the COVID-19 pandemic. Based on the results for the ratios of total asset turnover and fixed asset turnover, asset utilisation was less efficient. Analysis of the probability ratios and net profit margin showed a decrease in Pharmacy X’s profit during the pandemic. The Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI) values indicated that the business was less able to generate profits and net income from its invested capital.